2019
DOI: 10.1021/jacs.9b00594
|View full text |Cite
|
Sign up to set email alerts
|

Bi(I)-Catalyzed Transfer-Hydrogenation with Ammonia-Borane

Abstract: A catalytic transfer-hydrogenation utilizing a well-defined Bi(I) complex as catalyst and ammonia-borane as transfer agent has been developed. This transformation represents a unique example of low-valent pnictogen catalysis cycling between oxidation states I and III, and proved useful for the hydrogenation of azoarenes and the partial reduction of nitroarenes. Interestingly, the bismuthinidene catalyst performs well in the presence of low-valent transition-metal sensitive functional groups and presents orthog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
103
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(117 citation statements)
references
References 60 publications
1
103
0
2
Order By: Relevance
“…Thea bove structural features established for 2 through crystallography presented above are apparently retained in the solution phase over at least a100 8 8Ctemperature range as shown by ac ombination of variable-temperature 1 HNMR and solid-state 13 CNMR spectroscopy (see Figures S1 and S2).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Thea bove structural features established for 2 through crystallography presented above are apparently retained in the solution phase over at least a100 8 8Ctemperature range as shown by ac ombination of variable-temperature 1 HNMR and solid-state 13 CNMR spectroscopy (see Figures S1 and S2).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[12] One of these compounds was very recently shown to participate in redox catalysis traversing the Bi I /Bi III oxidation states. [13] Theg roup of Gilliard also reported aB i I complex formed by reduction of acarbene-Bi III halide adduct with Be 0 . [14] These compounds remain the only known examples of molecular bismuthinidenes,limiting the potential of Bi I chemistry.S ince they are apparently thermodynamically viable,t he inability to access a1 0-Bi-3 complex by mesomeric stabilization must be viewed as al igand design challenge,requiring aredox-active ligand that also introduces steric bulk to prevent over-coordination.…”
mentioning
confidence: 99%
“…[3] Radosevichh as done pioneeringw ork in evolvingn ew geometry constrained main-group compounds includings ystems featuring constrained P III triamidest hat exhibit catalytic activity (C). [8] Applications of tridentate-ligand-bound planarB i I compoundsi nc atalysis have now startedt oa ppear in work by Cornella, [9] following the comprehensive investigations by Breunig, Raţ, Nikonov,a nd Dostàlo fm onoanionic pnictogen N-C-N chelates. [5] Moving beyond phosphorus, tethered triamidel igands have been used by Dutton and Martin to achievea na pproximately T-shaped planargeometry at boron (F) [6] and by Greb to achieveseverely distorted tetrahedral arrangements at silicon that demonstrate noveld imerizationm odes (G).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Cornella et al. showed that the N,C,N‐chelated bismuth(I) compound (Figure A) was able to serve as a catalyst for the transfer hydrogenation of azo compounds and suggested that the catalytic cycle involves the Bi I −Bi III redox couple …”
Section: Figurementioning
confidence: 99%
“…[12] Recently,C ornella et al showedt hat the N,C,N-chelated bismuth(I) compound (Figure1A) wasa ble to serve as a catalystf or the transfer hydrogenation of azo compounds and suggested that the catalytic cycle involves the Bi I ÀBi III redox couple. [13] We have used similarh eavy pnictogen(I) compounds as ligands for transition metals [14] including those in which the antimony atom bridges two Pd atoms [15] ( Figure 1B). Here, we demonstrate that stibinidene ArSb (1)( where Ar = C 6 H 3 -2,6-(CH=NtBu) 2 )i sa ble to reversibly activate aC =Cd ouble bond in selected maleimides, therebys howing unprecedented reactivity in the fieldo fl ow-valent pnictogen(I) compounds.…”
mentioning
confidence: 99%